Assessment of Murine Neuroblastoma (N1E-115) Resting Membrane Potential by Confocal Microscopy - Hernandez, Miguel; Kisaalita, William S.; Farmer, Mark A. (Journal of Fluorescence, 1996)
Digital imaging (confocal microscopy) and a slow potentiometric dye (tetramethylrhodamine methyl ester) were used to assess the resting membrane potential (V m) of murine neuroblastoma cells (N1E-115). The averageV m was found to be −64.0±2.0 mV. The difference between this and the previously reported higher values was attributed to the use of glass microelectrode techniques that probably caused mechanical injury to the cell membranes: Digital imaging of N1E-115V m was found to be sensitive, reproducible, fast, and simple.